Public private partnership projects in Tanzania: A case of new Msamvu Bus Terminal- Morogoro - Wavii, Engais E. (Mzumbe University, 2024)
A Dissertation Submitted in Partial/Fulfillment of the Requirement for the Award of a Masters degree of Procurement and Supply Chain Management (MSC PSCM) of Mzumbe University,2019